Komunikasi Organisasi Antar Budaya di Lembaga Penjaminan Mutu Pendidikan Sumatera Utara - Rudianto Rudianto; Akhyar Anshori (UMSU, 2021)
This article is based on the background of the condition of organizational communication at the North Sumatra Education Quality Assurance Agency (LPMP) which involves staff with various cultural backgrounds. In particular, the difference between Civil Servants (PNS) who came from Java and those from North Sumatra. The main objective is to find out the patterns of interaction between civil servants from Java and local civil servants in the LPMP North Sumatra environment. This study was conducted through a qualitative method with an interpretive subjective approach in an effort to explain the phenomenon in depth through data collection by interview and observation. Data analysis in the form of inductive narrative through triangulation techniques. The results of this research found that due to differences in cultural backgrounds, civil servants from Java and local civil servants initially experienced problems in interacting. Civil servants from Java experienced a cultural shock in working at the North Sumatra LPMP because they entered a new place with a new culture from their place of origin. In their interactions, there is no marginalization between civil servants from Java and civil servants from Sumatra. Even though there are differences and conflicts, there is no time for exclusion of a civil servant because of his cultural and ethnic background.